2020
DOI: 10.5210/spir.v2020i0.11225
|View full text |Cite
|
Sign up to set email alerts
|

Youth in the Digital Age: Antecedents and Consequences of Digital Skills

Abstract: What actors and factors shape children and young people’s digital skills? And how do their digital skills impact the rest of their lives? These are the two research questions addressed in this paper, along with an analysis of how the research literature to date has measured digital skills. The findings reported here come from a systematic evidence review of the antecedents and consequences of digital skills (Haddon, Cino, Doyle, Livingstone, Mascheroni and Stoilova, forthcoming) as part of the ySKILLS project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 0 publications
3
26
0
Order By: Relevance
“…Interestingly, the results of the hierarchical multiple regressions (Table 3) identified few significant effects for the individual and social discrimination variables when compared to other predictors. Consistent with the literature on the antecedents of digital skills (Haddon et al, 2020), the most significant variables that account for higher levels of digital skills were parental mediation, age, gender, time spent online, preference for online social interaction, self-efficacy and personal attitudes towards the Internet. This suggests that SES and the variables of individual and social discrimination are not substantively associated with digital skills and do not offer much more information in the attempt to explain the variance in digital skills among European children who experience discrimination due to personal or social characteristics.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Interestingly, the results of the hierarchical multiple regressions (Table 3) identified few significant effects for the individual and social discrimination variables when compared to other predictors. Consistent with the literature on the antecedents of digital skills (Haddon et al, 2020), the most significant variables that account for higher levels of digital skills were parental mediation, age, gender, time spent online, preference for online social interaction, self-efficacy and personal attitudes towards the Internet. This suggests that SES and the variables of individual and social discrimination are not substantively associated with digital skills and do not offer much more information in the attempt to explain the variance in digital skills among European children who experience discrimination due to personal or social characteristics.…”
Section: Discussionsupporting
confidence: 77%
“…In line with previous studies that suggest that boys and girls develop different skills in different areas (van Deursen et al, 2016), boys have been found to report higher levels of digital skills, and this gender difference was larger among those children who felt discriminated against. While the reason for this difference may be a matter of variation in overall self-efficacy and perceived Internet self-confidence rather than of different competences (Haddon et al, 2020), it is important to note that a gender gap in digital skills may be further exacerbated in the case of individual and social discrimination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the current article is focused on digital skills (DS) as part of 21st-century skills. Previous publications defined six sub-skills of the (DS): digital information skills, digital communication skills, digital collaboration skills, critical thinking digital skills, creative digital skills, and problem-solving digital skills, as in the following concepts ( Table 1 ) [ 13 , 14 , 15 , 20 , 21 , 22 , 23 ].…”
Section: Literature Reviewmentioning
confidence: 99%